Anthelmintic efficacy of the modern antiparasitic drug Ivermitel (suspension) in toxocariasis invasion of dogs - Melnychuk, V.; Yanenko, D.; Yevstafieva, V. (Scientific Progress & Innovations, 2025)
The issue of preserving the health of animals from parasitic diseases is taken quite seriously by veterinary specialists, since in this case we are talking not only about the health of animals, but also about people. It is well known that many animal diseases of parasitic etiology can be transmitted to humans. One of these diseases is toxocariasis, in the spread of which dogs play an extremely important role. In dogs, the disease is caused by the nematode Toxocara canis (Werner, 1782) Stiles, 1905, where this nematode in the larval stage is able to parasitize in the human body. Therefore, timely therapeutic and preventive measures carried out among dogs using highly effective antiparasitic drugs are the key to the health of both animals and people. Considering the above, the aim of the work was to determine the therapeutic efficacy of the complex antiparasitic drug Ivermitel (suspension) in the presence of toxocariasis in dogs. To conduct a study to determine the therapeutic efficacy of the complex antiparasitic drug, two groups of dogs (experimental and control) were formed, each with an average intensity of invasion from 117.4 to 123.4 toxocar eggs in 1 g of feces. The experimental group of dogs was individually fed the drug Ivermitel (suspension) for therapeutic purposes by adding it to a small amount of treat food at a dose of 1 ml/kg of animal weight. The specified drug contains three active ingredients – praziquantel, pyrantel pamoate and ivermectin, two of which have a detrimental effect on nematodes. According to the results of the conducted studies, it was established that the drug Ivermitel (suspension) used in dogs with toxocariasis has pronounced anthelmintic properties against the pathogen Toxocara canis. In addition, during the period of observation of the animals, the drug does not cause side effects and reactions. The extent and intensity effectiveness of the drug used in toxocariasiс invasion of dogs one day after its application were 14.3 and 85.2 %, respectively. On the 2nd day after its application, the level of EE and IE increased to 28.6 and 94.9 %, respectively. On the 3rd day, the EE and IE indicators were 57.1 and 97.1 %, respectively. Starting from the 4th day and until the end of the experiment, the EE and IE of the drug was 100 %. Thus, the effectiveness of the complex antiparasitic drug Ivermitel (suspension) in accordance with the recommendations of the World Association for the Promotion of Veterinary Parasitology (W.A.A.V.P.) according to the activity index of anthelmintic chemicals for toxocariasiс invasion of dogs corresponds to the 1st efficiency class, namely it is highly effective.